Insufficiency of the luteal phase in infertility - Jefferson Cortéz, Luz (2015)
29 cases of luteal insufficiency of 634 infertile patients Arzobispo Loayza Hospital corresponding to an incidence of 4.5% were checked. The diagnosis was made by the findings of the endometrial biopsy in 68% of cases found other factors associated with infertility. In the treatment of clomiphene, bromocriptine or 17 hydroxyprogesterone caproate, yielding 9 pregnancies (31%).